Efficient free-space optical switching harnessing quasi-guided modes in a corrugated lithium niobate grating - Hui Jiang; Esha Maqbool; Zhanghua Han (Results in Physics, 2024)
We report and demonstrate an efficient free-space optical switching scheme by harnessing the high-Q resonances of quasi-guided modes (QGMs) supported by a corrugated Lithium Niobate grating on a slab waveguide. The well-confined guided modes in the slab are inaccessible by free-space radiations, so the incident light has a transmittance close to unity. However, when the refractive index of every second ridge is changed by Pockels effect at the presence of an applied voltage, the grating period increases by a factor of 2, leading to the transition from the guided modes into QGMs. The QGMs possess ultra-high Q factors allowing their efficient excitation through incident radiations, and then a near-zero transmittance at the wavelength of the QGM resonance is observed. The large contrast in the optical transmittance between the cases w/ and w/o the applied voltage shows that an efficient optical switch is achieved. Although the ultra-high Q factors of the QGMs make it challenging to match the working wavelength to the resonance, we further depict that this problem can be addressed by exploiting the large spatial dispersion of the QGMs, which enables an easy tuning of the resonance to a certain wavelength by changing the incident angle.